ANALISIS PENENTUAN PRIORITAS PEMELIHARAAN BANGUNAN DENGAN METODE â€ANALYTICAL HIERARCHY PROCESSâ€ PADA BANGUNAN GEDUNG CREATIVE SPACE UNICORN - SURABAYA - M. Roudlloh Nur Kusuma putra; Michella Beatrix (Racic : Rab Construction Research, 2024)
according to the requirements and wishes of the user. This research uses the "Analytical Hierarchy Process (AHP)" method, as a decision maker in determining the order of maintenance priorities by analyzing component condition indices. From the results of the analysis, it was found that the level of damage was based on the Condition Index value for the Creative Space Unicorn Building. It shows that the priority for building maintenance is the first architectural component in wall paint with a percentage of 1.16, the second utility, namely lights, has a percentage value of 0.79... So It can be concluded that the Creative Space Unicorn Building has a building condition index on a scale of 72.04. means that the description of the condition of the building is sufficient (only minor damage occurred).